Catalytic Cracking of Polypropylene-Low Density Polyethylene Pyrolysis Oil over Hierarchical H-ZSM-5 Catalyst - Dwi Cahyani, Silvia; Marlinda, Lenny; Evrianti, Yuli; Rimawan, Bagas; Heriyanti, Heriyanti; Rahmi, Rahmi; Sutrisno, Sutrisno (IPTEK The Journal for Technology and Science, 2024)
The conversion of plastic waste into liquid fuel has become the center of attention by researchers as a way to overcome environmental problems. According to last research, the polypropylene (PP) and low-density polyethylene (LDPE) pyrolysis oil mixture was classified into hydrocarbon range diesel which have the number of carbon atom from C12-C24. Because that, the effect of LDPE/PP pyrolysis oil over hierarchical H-ZSM-5 catalyst on hydrocarbon composition of liquid fuel oil using the catalytic cracking reactor at 200 oC was investigated. Hierarchical H-ZSM-5 catalyst (hH-ZSM-5) was obtained from H-ZSM-5 modified by desilication method using NaOH. Gas chromatography-mass spectrometry showed that the liquid fuel oil from the catalytic cracking of all variations consisted of aliphatic hydrocarbons with some cycloaliphatic compounds. In ratio of 250 mL/0.5 g (oil/catalyst) aromatic hydrocarbon increased from 1.69 area% to 15.58 area% over H-ZSM5 and hH-ZSM-5 respectively. The higher oil quality with shorter hydrocarbon chains in all variations was obtained over hH-ZSM-5 catalyst, namely in the range of C7-C14 or comparable to hydrocarbon range gasoline and kerosene.